The value of spot urinary creatinine as a marker of muscle wasting in patients with new‐onset or worsening heart failure. Issue 3 (20th March 2021) - Pandhi, Paloma; Streng, Koen W.; Anker, Stefan D.; Cleland, John G.; Damman, Kevin; Dickstein, Kenneth; Pellicori, Pierpaolo; Lang, Chim C.; Ng, Leong; Samani, Nilesh J.; Zannad, Faiez; Metra, Marco; et al.
Abstract: Background: Muscle wasting and unintentional weight loss (cachexia) have been associated with worse outcomes in heart failure (HF), but timely identification of these adverse phenomena is difficult. Spot urinary creatinine may be an easily accessible marker to assess muscle loss and cachexia. This study investigated the association of urinary creatinine with body composition changes and outcomes in patients with new‐onset or worsening HF (WHF). Methods: In BIOSTAT‐CHF, baseline spot urinary creatinine measurements were available in 2315 patients with new‐onset or WHF in an international cohort (index cohort) and a validation cohort of 1431 similar patients from Scotland. Results: Median spot urinary creatinine concentrations were 5.2 [2.7–9.6] mmol/L in the index cohort. Median age was 69 ± 12 years and 73% were men. Lower spot urinary creatinine was associated with older age, lower height and weight, worse renal function, more severe HF, and a higher risk of >5% weight loss from baseline to 9 months (odds ratio = 1.23, 95% CI = 1.09–1.39 per log decrease; P = 0.001). Spot urinary creatinine was associated with Evans criteria of cachexia (OR = 1.26 per log decrease, 95% CI = 1.04–1.49; P = 0.016) and clustered with markers of heart failure severity in hierarchical cluster analyses. Lower urinary creatinine was associated with poorer exercise capacity and quality of life (both P < 0.001) and predicted a higher rate for all‐cause mortality [hazard ratio (HR) = 1.27, 95% CI = 1.17–1.38 per log decrease; P < 0.001] and the combined endpoints HF hospitalization or all‐cause mortality (HR = 1.23, 95% CI = 1.15–1.31 per log decrease; P < 0.001). Significance was lost after addition of the BIOSTAT risk model. Analyses of the validation cohort yielded similar findings. Conclusions: Lower spot urinary creatinine is associated with smaller body dimensions, renal dysfunction, and more severe HF in patients with new‐onset/WHF. Additionally, lower spot urinary creatinine is associated with an increased risk of weight loss and a poorer exercise capacity/quality of life. Urinary creatinine could therefore be a novel, easily obtainable marker to assess (risk of) muscle wasting in HF patients.